Nord Streams projects in the field of cooperation between Russia and the European Union in the gas sector - Rakhimova М.А.; Yelmurzaeva Р.С.; Kakenova Г.М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
The article considers the key issues of cooperation between Russia and the European Union in the energy sector through the prism of the Nord Streams. Analysis of the gas industry is presented in the global format as well as part of the relationship between Russia and the European Union in particular. The Nord Streams are considered as the main gas pipelines of Russia. Along with economic are shown political factors affecting cooperation delivery between the RF and the EU in the gas sector. The authors of the article made an attempt to accumulate the results achieved in the implementation of the Nord Streams agreements, as well as give an analysis of ways to solve the problems.